Estimating Economic Losses due to Coastal Flooding in Medan Belawan, Indonesia - Hafiza Fikri Naipospos; Taryono Taryono; Zairion Zairion; Fery Kurniawan (International Journal of Economics and Management Research, 2026)
Coastal flooding is a recurring environmental hazard in Medan Belawan, driven by sea-level rise, land subsidence, and extreme tidal conditions. This study analyses the spatial distribution of coastal inundation in July 2025 and estimates the resulting economic losses across three affected sectors: households, business units, and public facilities. Spatial inundation mapping was conducted using DEMNAS elevation data combined with Highest High Water Level (HHWL) measurements, revealing that 79.5% of the study area (2,266 ha) was inundated. Primary data were collected through proportional random sampling involving 229 respondents and business/facility units across six urban villages. The estimated total economic loss reached IDR6.05 billion per month, consisting of IDR4.75 billion from household losses, IDR291 million from business units, and IDR1.01 billion from public facilities. Household losses were dominated by asset damage and income reduction, while business units experienced operational disruptions and decreased revenue. Public facilities faced structural damage and interruptions to basic services. These findings highlight significant economic impacts associated with the spatial extent and intensity of coastal flooding in low-lying coastal neighbourhoods of Medan Belawan.